2015
DOI: 10.1177/0308022615581312
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative evaluation of occupational therapy-led work rehabilitation for people with inflammatory arthritis: Perspectives of therapists and their line managers

Abstract: IntroductionOccupational therapy-led work rehabilitation for employed people with inflammatory arthritis and work problems was piloted in five hospitals in the United Kingdom. This qualitative study explored the views of participating occupational therapists and their line managers about the work rehabilitation training received and conducting the intervention, with particular focus on the structured interview used, the Work Experience Survey – Rheumatic Conditions.MethodFace-to-face semi-structured interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…This work highlights the need for more involvement of specialist nurses with appropriate training and social care personnel, which has also been suggested for patients with rheumatoid arthritis. 32 , 33 Moreover, the employer perspective is routinely missing in the wider rheumatology literature, possibly due to lack of focus and support for the relationship between health and the workplace. Despite the existence of OH departments, patients in this study reported a need for educating their managers/employers themselves with information about SLE.…”
Section: Discussionmentioning
confidence: 99%
“…This work highlights the need for more involvement of specialist nurses with appropriate training and social care personnel, which has also been suggested for patients with rheumatoid arthritis. 32 , 33 Moreover, the employer perspective is routinely missing in the wider rheumatology literature, possibly due to lack of focus and support for the relationship between health and the workplace. Despite the existence of OH departments, patients in this study reported a need for educating their managers/employers themselves with information about SLE.…”
Section: Discussionmentioning
confidence: 99%
“…We also conducted interviews with participants and the occupational therapists to investigate their views of VR and the work advice provided [ 30 , 31 ]. Intervention group participants valued the VR, particularly the training in work-based pain and fatigue self-management, joint protection, pacing, ergonomic and job adaptations/ accommodations advice.…”
Section: Discussionmentioning
confidence: 99%
“…Most participants in both groups had either not read the self-help work information or considered it had little impact [ 30 ]. The occupational therapists considered: the VR was beneficial for patients; and they could now provide a more comprehensive and individualised VR service [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prevention of work disability is particularly important as work is often not a treatment goal for those who cease to be employed; therefore, once people with RA stop work, they are unlikely to start again (Hammond, 2004). Work interventions for job retention might therefore be more effective than strategies to regain it (Prior and Hammond, 2014a; Prior et al., 2015).…”
Section: Introductionmentioning
confidence: 99%